Micro-flow imaging for in-situ and real-time enumeration and identification of microplastics in water - Choran, Nimitha; Örmeci, Banu (Frontiers in Water, 2023)
Microplastics (MPs) are emerging contaminants that have recently gained global attention. Current identification and quantification methods are known to be time-consuming, labour-intensive, and lack consensus on protocol standardization. This study explored the potential of micro-flow imaging (MFI) technology for rapid and in-situ identification and enumeration of MPs in water using two (2) MFI-based particle counters. Advantages, limitations, and recommendations for using MFI for MPs analysis were discussed. MPs with diverse physical (i.e., microbeads, fragments, fibres, and films) and surface (i.e., reflectivity, microporosity, colour) characteristics were analyzed to understand the detection capabilities and limitations of MFI technology. Results demonstrated that MFI effectively automates most manually obtained particle features, such as size, colour, object intensity and shape descriptors. It imparts consistency and reduces the subjective nature of results, thus enabling reliable comparison of the generated data. The particles can be further categorized based on their circularity and aspect ratio providing further insight into the shape and potential erosion of MPs in the environment. Transparent particles, often missed with other techniques such as microscopy, were detected by the MFI technology. The ability to assign particle IDs to MPs was an important advantage of the MFI technology that enabled the further investigation of selected MPs of interest. The limitations of the MFI technology were apparent in samples with high particle concentrations, with reflective MPs, and in the presence of bubbles. The colour of the background against which the image was captured also influenced the detection accuracy. Procedural modifications during sample analysis and improvements in image analysis can assist in overcoming these challenges. MFI requires minimal sample preparation and gives real-time imaging data, making it a prime candidate for field monitoring in surface water systems in addition to laboratory analysis. With the potential application of machine learning and similar developments in the future, MFI-based particle counters are well-positioned to meet an important need in in-flow and real-time identification and enumeration of MPs.